Pluvial spacionalizations by the krigage method in the hydrographic basin of the alto rio Paraíba, Brazil (Research, Society and Development, 2022)
In order to better analyze the climate of a given region, it is necessary to characterize its constituent elements as to the historical precipitation around the Paraíba river hydrographic basin. The objective is to analyze and elaborate monthly, annual, rainy and dry periods, rainy and dry four-month periods and rainy and dry months estimated by the kriging method based on the historical average of the last fifty-six years in the Paraíba River hydrographic basin. A series of monthly and annual rainfall data for the period 1962–2018 was used, except for the municipalities of Caraúba and Coxixola where their period was different; the data were collected by the Northeast Development Superintendence and provided by the Executive Agency for the Management of Waters of the State of Paraiba. The Krigagem interpolation model was significant with the results presented. The annual rainfall distribution shows high spatial variability in the study area. Irregular precipitations caused by long periods of summer, that is, rainfall with irregular spatial and temporal distribution, causing water deficits, with direct effects on agricultural crops, such as reduced plant development, abortion and fall of flowers, grain filling or even the total loss of the plantation, generating water scarcity for human, animal and vegetable supply, damming of water in the dams and socioeconomic impacts.